Increased resting heart rate indicates high-workload hearts with augmented aortic hydraulic power in hypertensive pigs - Pao-Yen Lin; Bo-Wen Lin; Tong-Sian Lai; Yan-Hsiang Yang; Meei Jyh Jiang (PLoS ONE, 2025)
Clarifying the inceptive pathophysiology of hypertensive heart disease helps to impede the disease progression. Through coarctation of the infrarenal abdominal aorta (AA), we induced hypertension in minipigs and evaluated physiological reactions and morpho-functional changes of the heart. Moderate aortic coarctation was achieved with approximately 30 mmHg systolic pressure gradient in minipigs. Hypertension was assessed by pressure increment of the carotid artery. Perioperative heart rate (HR) was recorded. We measured aortic flow rate and pressure proximal to coarctation to calculate hydraulic power, an indicator for cardiac workload, and resistance. The hearts harvested at sacrifice were examined for myocardial hypertrophy, fibrosis, and dysfunction. The parameters capable of indicating high-workload heart and their prediction effectiveness were determined by cluster and receiver operating characteristic (ROC) analyses. Prolonged AA coarctation for 8–12 weeks induced hypertension in a portion of minipigs. The cluster of minipigs exhibiting increased aortic hydraulic power displayed hypertension and mean HR elevation without changing arterial resistance. Notably, the blood pressure and HR were measured under full anesthesia, equivalent to resting status. Myocardial hypertrophy was not detected at the tissue, cellular or molecular levels. Expression of biomarkers for cellular stress and heart failure didn’t increase except for heat shock protein 40. ROC analysis showed that aortic hydraulic power, resting HR, and mean blood pressure, but not arterial resistance, can serve as the indicators for high-workload hearts. These results suggested that resting HR increase in hypertensive pigs indicates hearts with high workload. Heart failure may develop without appropriate treatment.